The influence of obesogenic environments on diet self-efficacy and physical activity among healthcare workers: a multicenter study - Sezerol, Mehmet Akif; Altaş, Zeynep Meva; Aslan, Melek Nur; Halaç, Şeyma (My University, 2024)
Background: The aim of the study was to determine the level of dietary self-efficacy, physical activity and obesogenic environment in several districts of Istanbul and to examine the relationship between them. Methods: In this cross-sectional study, a questionnaire was administered to primary health care workers working in three different districts of Istanbul. Sociodemographic questions, Dieting Self-Efficiency Scale (DSES), The Assessment of the Obesogenic Environment Scale (AOES), and International Physical Activity Questionnaire (IPAQ) were used in the survey. p < 0.05 was determined as the level of statistical significance. Results: A total of 639 healthcare workers responded to the study. The median age of the participants was 39.0 years (min-max: 21.0–67.0). Male and single participants had significantly higher DSES scores (p = 0.014, p = 0.016, respectively). Male participants and those with lower income and education level had significantly higher scores on the AOES (p = 0.025, p = 0.024 and p = 0.024, respectively). According to the IPAQ, 56.8% (n = 283) of the participants were minimally physically active, 29.7% (n = 148) were inactive and 13.5% (n = 67) were very active. Those who were physically minimally active and very active had significantly higher DSES scores and significantly lower AOES scores than those who were inactive (p < 0.001 and p = 0.011). There was a significant negative correlation between the DSES and AOES (r=-0.263, p < 0.001). Conclusion: In this study, the evaluation of the concepts of dietary self-efficacy, physical activity level and obesogenic environment in healthcare professionals, who can be role models in the society, may contribute to the studies and intervention strategies for the whole society.
Keywords: Diet; Healthcare Workers; Obesogenic Environment; Physical Activity; Self-Efficacy